Physicochemical Properties of Flaxseed Fortified Extruded Bean Snack - Naveen Vadukapuram; Clifford Hall; Mehmet Tulbek; Mary Niehaus (International Journal of Food Science)
Milled flaxseed was incorporated (0–20%) into a combination of bean-corn flours and extruded in a twin screw extruder using corn curl method. Physicochemical parameters such as water activity, color, expansion ratio, bulk density, lipid content, and peroxide values of extruded snack were analyzed. Scanning electron micrographs were taken. Peroxide values and propanal contents were measured over four months of storage. Rancidity scores of extruded snack were measured using a trained panel. As expected, omega-3 fatty acids and bulk density increased with increasing flaxseed fortification levels. Extrudates with more flaxseed had decreased lightness values and expansion ratios. However, only the 15 and 20% flaxseed containing extrudates had expansion ratios that were significantly (P≤0.05) different from the control. In general, no significant difference (P>0.05) in water activity values was observed in the flaxseed fortified extrudates, except in the navy-corn based extrudates. Peroxide values increased with increased flaxseed levels and over a storage period. However, propanal values did not change significantly in the 5–10% flaxseed fortified extrudates but increased in extrudates with higher levels of flaxseed. Rancidity scores were correlated with peroxide values and did not increase significantly during storage under nitrogen flushed conditions.